2017
DOI: 10.3892/ol.2017.5673
|View full text |Cite
|
Sign up to set email alerts
|

miR-198 functions as a tumor suppressor in breast cancer by targeting CUB domain-containing protein 1

Abstract: Abstract. The molecular mechanisms underlying the dysregulation of microRNAs (miRs) have been previously documented in breast cancer. miR-198 has been reported to be deregulated in several human cancers. However, the detailed effects of miR-198 on breast cancer progression remain unclear. Using quantitative polymerase chain reaction analysis, we demonstrated in the present study that miR-198 was downregulated in breast cancer tissues and cell lines, and that downregulation of miR-198 was significantly correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“… 7 Moreover, the significance of miRNAs in breast cancer has been documented by a study. 8 For example, miR-198 inhibited cell proliferation and migration and promoted cell adhesion in aggressive breast cancer by targeting CUB domain-containing protein 1 (CDCP1); 9 miR-340 suppressed the migration, invasion, and metastasis of breast cancer cells through modulating Wnt/β-catenin signaling pathway; 10 miR-148a accelerated cell apoptosis and restricted growth of breast cancer cells via regulating B-cell lymphoma 2 (Bcl-2). 11 Therefore, miRNAs are regarded as reliable prognostic markers, promising therapeutic targets, or new drugs, which would be essential in the prevention and treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Moreover, the significance of miRNAs in breast cancer has been documented by a study. 8 For example, miR-198 inhibited cell proliferation and migration and promoted cell adhesion in aggressive breast cancer by targeting CUB domain-containing protein 1 (CDCP1); 9 miR-340 suppressed the migration, invasion, and metastasis of breast cancer cells through modulating Wnt/β-catenin signaling pathway; 10 miR-148a accelerated cell apoptosis and restricted growth of breast cancer cells via regulating B-cell lymphoma 2 (Bcl-2). 11 Therefore, miRNAs are regarded as reliable prognostic markers, promising therapeutic targets, or new drugs, which would be essential in the prevention and treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs participate in the modulation of greater than one-third of human genes (10). Studies have indicated that miRNAs are dysregulated in various types of human cancers, such as gastric cancer (11), hepatocellular carcinoma (12), bladder cancer (13), ovarian cancer (14) and breast cancer (15). Abnormally expressed miRNAs have been implicated in tumour initiation and progression, and may regulate a variety of important physiological events, including cell proliferation, cell cycle, apoptosis, angiogenesis, migration and invasion and metastasis (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-198-5p has been reported to be upregulated in multiple myeloma [ 14 ], chronic pancreatitis or pancreatic ductal adenocarcinoma [ 15 ], Parkinson’s disease [ 16 ], esophageal cancer [ 17 ], preeclampsia [ 18 ], pancreatic adenocarcinoma, ampullary adenocarcinoma [ 19 ], lupus nephritis [ 20 ], retinoblastoma [ 21 ], anencephaly [ 22 ], and squamous cell carcinoma of tongue [ 23 ]. On the other hand, low expression of miR-198-5p has been found in prostate cancer [ 24 ], breast cancer [ 25 ], glioblastoma [ 26 , 27 ], hepatocellular carcinoma [ 28 ], especially hepatitis C virus-associated hepatocellular carcinoma [ 29 , 30 ], osteosarcoma [ 31 ], gastric cancer [ 32 ], colorectal cancer [ 33 ], pancreatic cancer [ 34 ], and respiratory syncytial virus (RSV) infection [ 35 ]. The overexpression of miR-198-5p has also been documented in CD8+ T cells in renal cell carcinoma [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma, miR-198-5p has been shown to target the HGF/c-MET pathway [ 38 ]. Several studies have revealed that the expression of miR-198-5p is greatly related to lymph node metastasis or distant metastasis in different malignant diseases, such as breast cancer [ 25 ], osteosarcoma [ 31 ], gastric cancer [ 32 ], and colorectal cancer [ 33 ]. Some studies have also shown that miR-198-5p is closely related to cell proliferation, apoptosis, and migration [ 12 , 14 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%